Functional analysis of an R311C variant of Ca2+‐calmodulin‐dependent protein kinase kinase‐2 (CaMKK2) found as a de novo mutation in a patient with bipolar disorder. (9th April 2020) - XY Ling, Naomi; Langendorf, Christopher G.; Hoque, Ashfaqul; Galic, Sandra; Loh, Kim; Kemp, Bruce E.; Gundlach, Andrew L.; Oakhill, Jonathan S.; Scott, John W.
Abstract: Objectives: Loss‐of‐function mutations in the gene encoding the calcium‐calmodulin (Ca 2+ ‐CaM)‐dependent protein kinase kinase‐2 (CaMKK2) enzyme are linked to bipolar disorder. Recently, a de novo arginine to cysteine (R311C) mutation in CaMKK2 was identified from a whole exome sequencing study of bipolar patients and their unaffected parents. The aim of the present study was to determine the functional consequences of the R311C mutation on CaMKK2 activity and regulation by Ca 2+ ‐CaM. Methods: The effects of the R311C mutation on CaMKK2 activity and Ca 2+ ‐CaM activation were examined using a radiolabeled adenosine triphosphate (ATP) kinase assay. We performed immunoblot analysis to determine whether the R311C mutation impacts threonine‐85 (T85) autophosphorylation, an activating phosphorylation site on CaMKK2 that has also been implicated in bipolar disorder. We also expressed the R311C mutant in CaMKK2 knockout HAP1 cells and used immunoblot analysis and an MTS reduction assay to study its effects on Ca 2+ ‐dependent downstream signaling and cell viability, respectively. Results: The R311C mutation maps to the conserved HRD motif within the catalytic loop of CaMKK2 and caused a marked reduction in kinase activity and Ca 2+ ‐CaM activation. The R311C mutation virtually abolished T85 autophosphorylation in response to Ca 2+ ‐CaM and exerted a dominant‐negative effect in cells as it impaired the ability of wild‐type CaMKK2 to initiate downstream signaling and maintain cell viability. Conclusions: The highly disruptive, loss‐of‐function impact of the de novo R311C mutation in human CaMKK2 provides a compelling functional rationale for being considered a potential rare monogenic cause of bipolar disorder.